Improving Students' Reading Skills Through the Use of the Storytelling Method in Elementary School Students - Gusni Efin; Paldy Paldy; Haspidawati Nur (CV. Edujavare Publishing, 2026)
One of the basic competencies that must be developed in elementary school is language skills which include listening, speaking, reading, and writing. This study aims to improve students' reading skills through the use of the storytelling method in grade III students at SDN 42 Limpomajang, Palopo City. This type of research is class action research (PTK). The subjects in this study are grade III students totaling 10 students. The research instruments used were reading tests, observation of learning implementation, and observation of student activities. The data analysis technique used is quantitative descriptive. The results of the study show that the average test score on students' reading skills increased through the use of the storytelling method in grade III of SDN 42 Limpomajang, Palopo City, where the increase that occurred from cycle I to cycle II was 20% This is evidenced by the results of the research where the first cycle obtained student learning outcomes by 60% and the second cycle obtained learning outcomes by 80%.